2023
DOI: 10.1021/acsestwater.3c00183
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Metagenomic Sequencing for Detection of Vertebrate Viruses in Wastewater for Public Health Surveillance

Camille McCall,
Ryan A. Leo Elworth,
Kristine M. Wylie
et al.

Abstract: Viruses of concern for quantitative wastewater monitoring are usually selected as a result of an outbreak and subsequent detection in wastewater. In addition, targeted metagenomics could proactively be used for widespread identification and sequencing of viruses of concern when used as an initial screening tool. To evaluate the utility of targeted metagenomics for wastewater screening, we used ViroCap, a panel of probes designed to target all known vertebrate viruses. Untreated wastewater was collected from wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Beyond the concentration and extraction method, the sensitivity of probe-capture sequencing will likely vary with the probe panel selected and the seasonal fluctuations in wastewater microbial composition. In the present study and other studies using broad virus capture panels, , human virus sequences were predominantly enteric virus targets present in the panel, such as mamastrovirus, and the detection of SARS-CoV-2 was limited. However, several studies using the narrower RVOP panel found remarkably high coverages of SARS-CoV-2, surpassing other respiratory human viruses included in the panel. ,, Another study also found that the share of sequences derived from SARS-CoV-2 was higher when using the Respiratory Virus Oligo Panel (RVOP) than the broader Respiratory Pathogen ID/AMR Panel (RPIP), which included other high-abundance targets .…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Beyond the concentration and extraction method, the sensitivity of probe-capture sequencing will likely vary with the probe panel selected and the seasonal fluctuations in wastewater microbial composition. In the present study and other studies using broad virus capture panels, , human virus sequences were predominantly enteric virus targets present in the panel, such as mamastrovirus, and the detection of SARS-CoV-2 was limited. However, several studies using the narrower RVOP panel found remarkably high coverages of SARS-CoV-2, surpassing other respiratory human viruses included in the panel. ,, Another study also found that the share of sequences derived from SARS-CoV-2 was higher when using the Respiratory Virus Oligo Panel (RVOP) than the broader Respiratory Pathogen ID/AMR Panel (RPIP), which included other high-abundance targets .…”
Section: Resultsmentioning
confidence: 56%
“…All human virus species detected (>10 reads per species) in at least one sample were compared across the four methods (Figure ). Some viruses were consistently detected by all methods, including human polyomavirus, mastadenovirus, mamastrovirus 1, and norwalk virus, which were included in the VSP probe set and are known to be shed at high concentrations in human waste. ,,,,,, RNA virus species, including severe acute respiratory syndrome-related coronavirus, sapporo virus, and enteroviruses, were not detected in NT and Solids samples. Different trends were also observed among virus species within the same genus.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Child et al applied both RVOP and RPIP in parallel and reported lower coverage of SARS-CoV-2 with RPIP, likely due to competition for sequencing with other targets . Several other studies applied very broad panels covering major groups of human viruses and reported that the predominant human virus was Mamastrovirus followed by other enteric viruses, while respiratory viruses were at lower relative abundance sometimes by orders of magnitude. , , Although differences in samples, sample processing, and bioinformatics make direct comparisons impossible (Table ), these results point to trade-offs in probe panel selection.…”
Section: Probe Set Selection Hybridization and Sequencing Depthmentioning
confidence: 99%
“…Several pan-viral probe panels designed prior to the COVID-19 pandemic (i.e., panels lacking probes for SARS-CoV-2) were able to recover partial SARS-CoV-2 genomic sequences from clinical samples with high viral concentrations. Additionally, the high-level multiplexing available with probe capture provides an opportunity to surveil a broad range of viruses in wastewater, capturing disease dynamics for pathogens lacking comprehensive clinical surveillance . Several targeted virus sequencing panels have recently been applied to wastewater samples, including Illumina Respiratory Virus (RVOP), Virus Surveillance (VSP), , and Respiratory Pathogen/AMR (RPIP), , VirCapSeq-VERT, ViroCap, , Twist Comprehensive Virus Capture Panel, and Qiagen xHyb Adventitious . When compared to untargeted sequencing, probe capture enrichment was found to successfully increase target virus relative abundance by orders of magnitude (Table ).…”
Section: Introductionmentioning
confidence: 99%